The role of job satisfaction and job stress in mediate the effect of organizational justice on deviant behavior in the workplace - Bhandesa, Wawan Mahajana; Wibawa, I Made Artha (International research journal of management, IT and social sciences, 2022)
Workplace deviant behavior is the behavior of members of the organization that is not in accordance with the rules or norms, general habits that serve as guidelines in the organization that have a negative impact on the organization and/or members of the organization. This study aims to determine the role of job satisfaction and job stress in mediating effect of organizational justice on workplace deviant behavior. This research was conducted on government employees in Udayana University with a sample of 106 employees. The samples were collected by using proportionate random sampling. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The result showed that job satisfaction was not able to mediate the effect of organizational justice on workplace deviant behavior and job stress was able to fully mediate the effect of organizational justice on workplace deviant behavior. These result showed that in order to reduce workplace deviant behavior, the leader’s must improve organizational justice that can increase job satisfaction and reduce job stress levels, so that the employee’s intention to behave defiantly in the workplace will be reduced.